Analisis Strategi Keberlanjutan Bisnis Makanan Sehat Woofle di Kota Palembang - Nelson Imannual Tenggara; Verah Verah; Charisma Ayu Pramuditha (Universitas Multi Data Palembang, 2026)
This study aims to analyze the development of the implementation of the Woofle healthy food business (gluten-free waffles) in Palembang City. Woofle is a gluten-free waffle product as a healthy food alternative that is safe for consumption by all groups, especially for consumers with a healthy lifestyle and those with celiac disease or gluten intolerance. The scope of this study includes product, marketing, and financial aspects with a quantitative descriptive research method processed from consumer interest and satisfaction questionnaire data. The results of the study show that Woofle is well received because it offers variant differentiation and the use of nutritious fresh fruit toppings with the majority of customers coming from students. The results of the financial analysis show that Woofle is able to generate stable profits so that business development is feasible to run and develop sustainably.